A study entrepreneurial orientation, ecommerce adoption, organizational culture, and dynamic business environment on textile SME performance in Pakistan - Abbas, Ali (2020)
Small and Medium Enterprises (SMEs) play an important part in the economy of Pakistan. SME sector of Pakistan represent approximately 90% of all the enterprises in Pakistan. SMEs shared about 40% in the annual GDP of the country. Within the SMEs, the textile industry of Pakistan contributes around 40% of employment of the total industrial labour force. The textile industry in Pakistan used to be an important export-oriented industry and it was one of the primary sources of foreign exchange. However, since 2013 Pakistan is quickly and continuously losing its market share. Consequently, the Pakistani textile exports dropped dramatically by 26.19% in 2018. The main objective of this study is to examine the relationships between entrepreneurial orientation, e-commerce adoption, organizational culture, and financial and non-financial performance of SMEs in Pakistan. In addition, this study also assesses the moderating role of dynamic business environment on these relationships. Twelve hypotheses were developed to answer the RQ and achieve RO. Data was collected from the Pakistani textile SMEs registered with the Lahore Chamber of Commerce & Industries using a cross-sectional study design. The study used single stage cluster sampling method. Questionnaires were distributed to 520 respondents which were randomly selected from the population. Partial Least Squares Structural Equation Modelling was used to test the study’s hypotheses. This study found that e-commerce adoption, organizational culture, dynamic business environment are important strategic orientations for the financial and non-financial performance of SMEs in Pakistan. The results of this study provide important insights to owner-managers, policy-makers and researchers to further understand the effects of e-commerce adoption, organizational culture and dynamic business environment on SMEs performance. Policy-makers should encourage SMEs to improve their cash flow, profit and retained earnings, which may encourage financial institutions to provide them with financial services.